Kemampuan Membaca Al-Qur’an dan Kejenuhan Belajar terhadap Metode Tunggal Siswa Kelas X SMA Negeri 4 Tuban : Sebuah Temuan dan Solusi Praktis - Nurul Laela; Kharisma Maya M; Ali Fauzi (Reflection : Islamic Education Journal, 2026)
The ability to read the Qur’an is a fundamental competence that must be possessed by every Muslim student. However, in educational practice at schools, various problems are still found, particularly the low level of Qur’an reading ability among some students, accompanied by learning boredom. One of the contributing factors to this condition is the use of a single, monotonous, and less varied teaching method. This article aims to examine the problems related to students’ ability to read the Qur’an and the learning boredom that arises due to the implementation of a single method in instruction, as well as to offer practical solutions that can be implemented by educators. The writing method of this article uses a literature review approach and reflection on teaching practice. The results of the study show that a single teaching method tends to reduce students’ learning motivation, hinder active engagement, and slow down the improvement of Qur’an reading skills. Therefore, it is necessary to implement more varied, interactive, and contextual teaching methods, such as game-based learning, group work, and the use of innovative instructional media. Thus, it is expected that students’ ability to read the Qur’an can improve and learning boredom can be effectively minimized.